Standardisation of electrocardiographic examination in corn snakes (Pantherophis guttatus). (1st June 2020) - Lewis, Martyn; Bouvard, Jonathan; Eatwell, Kevin; Culshaw, Geoff
Abstract : Introduction: Corn snakes are a very common pet reptile species, yet there is an absence of evidence‐based literature standardising collection of ECG or detailing ECG deflection morphology in the normal animal. The authors describe a well‐tolerated, reproducible technique and detail the cardiac cycle in terms of lead 2 equivalent waveforms and intervals. Animals: 29 adult corn snakes. Materials and methods: This prospective study evaluated, under species‐appropriate, standardised conditions, a technique for producing standard six‐lead ECG tracings. Lead 2 equivalent cardiac cycles were described in detail and statistically analysed for sex, weight, length, heart rate and mean electrical axis. Results: High‐quality tracings demonstrated common ECG characteristics for this species, including no Q, S or SV waves, prolonged PR and RT intervals, rhythmic oscillation of the baseline, short TP segments, and a right displaced mean electrical axis. An influence of sex, weight or length on heart rate and mean electrical axis was not identified. Conclusions: To the authors' knowledge, this is the first study to describe a standardised technique for recording ECG in significant numbers of normal corn snakes. Ranges have been provided that may be of diagnostic value or form the basis for future development of reference intervals for this species.